Etiology of pulp necrosis as a predictor of success in regenerative endodontics: a case report and bioinformatic analysis - Alcota, Marcela; Torres, Alfredo; Ledezma, Paulina; Mercado, Montserrat; Paredes, Paulina; González, Fermín E. (Frontiers in Dental Medicine, 2025)
Regenerative endodontics (RE) is a biologically based procedure designed to replace damaged dental structures, including dentin and root structures, and cells of the pulp-dentin complex. It is the first-line treatment for patients with immature permanent teeth (IPT) that have lost vitality due to dentoalveolar trauma (DAT), caries, or developmental anomalies such as dens evaginatus (DE). Beyond resolving clinical signs and symptoms, RE allows for continued root development, substantially improving the long-term prognosis of these cases. Here, we present a clinical case of a 12-year-old female patient who, as a result of dentoalveolar trauma, exhibits asymptomatic apical periodontitis of tooth 1.1 and chronic apical abscess of tooth 2.1 in IPT. Both teeth were treated with regenerative endodontics, achieving successful RE in tooth 2.1 and inducing apical closure with Biodentine in tooth 1.1. In addition, we conducted a bioinformatic analysis to identify key genes associated with the success of post-trauma RE, providing a more complete and mechanistic understanding of the factors determining treatment success. In conclusion, the success of RE procedures in IPT may be conditioned by the type of DAT suffered by the tooth. Moreover, incorporating bioinformatic analysis introduces an innovative approach to unravel the molecular mechanisms involved in post-trauma dental regeneration.